The Jurassic of Denmark and Greenland: Triassic and Jurassic transtension along part of the Sorgenfrei–Tornquist Zone in the Danish Kattegat - Korstgård, John a.; Mogensen, Tommy Egebjerg (Geological Survey of Denmark and Greenland, 2003)
In the Kattegat area, Denmark, the Sorgenfrei–Tornquist Zone, an old crustal weakness zone, was repeatedly reactivated during Triassic, Jurassic and Early Cretaceous times with dextral transtensional movements along the major boundary faults. These tectonic events were minor compared to the tectonic events of the Late Carboniferous – Early Permian and the Late Cretaceous – Early Tertiary, although a dynamic structural and stratigraphic analysis indicates that the Sorgenfrei–Tornquist Zone was active compared to the surrounding areas.At the end of the Palaeozoic, the area was a peneplain. Regional Triassic subsidence caused onlap towards the north-east, where the youngest Triassic sediments overlie Precambrian crystallinebasement. During the Early Triassic, several of the major Early Permian faults were reactivated, probably with dextral strike-slip along the Børglum Fault. Jurassic – Early Cretaceous subsidence was restricted primarily to the area between the two main faults in theSorgenfrei–Tornquist Zone, the Grenå–Helsingborg Fault and the Børglum Fault. This restriction of basin development indicates a change in the regional stress field at the Triassic–Jurassic transition. Middle Jurassic and Late Jurassic – Early Cretaceous subsidence followed the Early Jurassic pattern with local subsidence in the Sorgenfrei–Tornquist Zone, but now even more restrictedto within the zone. The subsidence showed a decrease in the Middle Jurassic, and increased again during Late Jurassic – Early Cretaceous times. Small faults were generated internally in theSorgenfrei–Tornquist Zone during the Mesozoic with a pattern that indicates a broad transfer of strike-slip/oblique-slip motion from the Grenå–Helsingborg Fault to the Børglum Fault.